Rapid polymerase chain reaction assays for Brevibacillus laterosporus detection. (28th June 2019) - Marche, Maria Giovanna; Mura, Maria Elena; Ruiu, Luca
Abstract: The identification of the ubiquitous spore‐forming bacterium Brevibacillus laterosporus, whose interest in pharma, agriculture, and other industrial sectors is raising, mostly relies on 16S ribosomal RNA gene sequence analysis. However, due to bacterial gene homology, this method appears insufficient for a proper discrimination of this species, so that the availability of other target genes is necessary. Leveraging the morphological and genetic feature uniqueness of B. laterosporus, a sensitive and reliable detection and quantification method based on polymerase chain reaction (PCR) and quantitative PCR assays, respectively, was developed. Targeting a highly conserved spore surface protein‐related gene, B. laterosporus could be easily found in different matrices including soil, food, and insect body. Primer set selectivity was confirmed to be very specific and no false positives or negatives were observed using DNA of different bacterial species as a template. The method developed is also suitable for the rapid identification of newly isolated B. laterosporus strains.